PENGARUH PENERAPAN STRATEGI ACTIVE LEARNING TIPE INSTANT ASSESSMENT DALAM PEMBELAJARAN MATEMATIKA TERHADAP PEMAHAMAN KONSEP SISWA KELAS VIII PUTRI (PI) SMP NURUL IKHLAS KABUPATEN TANAH DATAR - Anggela, Rani Valicia; Aima, Zulfitri; Yunita, Alfi (Pendidikan Matematika, 2013)
The research motivated by the studentsâ less understanding about the Â concept of mathematic. It seen from the results of mathematic test in the second semester of grade sevent that listed in grade VIII Putri (Pi) SMP Nurul Ikhlas in academic year 2013/2014 . One of the way to increase studentsâ understanding about the concept is applying Instant Assessment type of Active Learning strategy. The research purpose is to know whether studentsâ understanding in applying Instant Assessment type of Active Learning strategy is better than conventional learning for Â grade VIII Putri (Pi) SMP Nurul Ikhlas Tanah Datar .Kind of research is experimental research and the research design is randomized to the subject . The populations are the students of eighth grade Â of SMP Nurul Ikhlas that consist of 4 classes . where class VIII Pi 1 as experimental and class VIII Pi 2 as a control class . The instrumentation in the research is studentsâobservation activity sheet and tests students understanding of mathematicâs concept . the test is in essay from with a reliability value 0,77.Based on the result of data analysis, bpth of sample class are normal and homogen in Î± = 0.05 and the results of hypothesis tests by using MINITAB software is P - value = 0.018 < Î± . It can be concluded students understanding of concepts with applying Instant Assessment type of Active Learning strategy is better than the students understanding of concepts with conventional learning .